A qualitative exploration of how people with bipolar disorder consider risk-taking in everyday decisions. Issue 3 (18th May 2021) - Wah, Andrew; Hodge, Suzanne; Jones, Steven H.; Perez Algorta, Guillermo
Abstract: Background: Difficulties with decision making and risk taking in individuals with bipolar disorder (BD) have been associated with mood episodes. However, there is limited information about these experiences during euthymia, the mood state where people with BD spent the majority of their time. Aims: To examine how individuals with BD consider risk in everyday decisions during their euthymic phase. Method: We conducted a qualitative study that used semi-structured audio recorded interviews. Eight euthymic participants with confirmed BD were interviewed, and we used interpretative phenomenological analysis to analyse the data. Results: We identified four themes. The first theme, 'Who I really am', involves the relationship between individual identity and risks taken. The second theme, 'Taking back control of my life', explored the relationship between risks taken as participants strove to keep control of their lives. The third theme, 'Fear of the "what ifs"', represents how the fear of negative consequences from taking risks impacts risk decisions. Finally, the fourth theme, 'The role of family and friends', highlights the important role that a supporting network can play in their lives in the context of taking risks. Conclusions: The study highlights aspects that can impact on an individual with BD's consideration of risk during euthymia. Identity, control, fear and support all play a role when a person considers risk in their decision-making process, and they should be taken into consideration when exploring risk with individuals with BD in clinical settings, and inform the design of future interventions.